Theorems of Helly's Type for Partially-Closed Half-Spaces (Communications in Mathematical Research, 2019)
In this article, under quite weaker conditions, theorems of Helly's typefor (not necessarily finite) family of partially closed half-spaces are presented in bothanalytic and geometric forms. Examples are also provided to show that these conditions cannot be omitted in general.